Hydrothermal Synthesis and Structural Properties of V2O5 Nanoflowers at Low Temperatures - Abd-Alghafour, N. M.; Ahmed, Naser. M.; Hassan, Z.; Almessiere, Munirah Abdullah (2017)
Vanadium pentoxide nanoflowers were synthesized through a simple hydrothermal method at low temperatures. The structure was fabricated by using NH4VO3 and oxalic acid as precursors with 0.1 M solution concentration. The morphology and structural properties of the nanoflowers were characterized using FESEM, XRD, Raman, and UV-Visible spectroscopy. The results reveal an orthorhombic structure with preferred orientation along (001) plane of the prepared V2O5 nanoflowers. Raman peaks also expressed the same structural features. FESEM images showed the V2O5 nanoflower with diameters in the range of 60-80 nm and length in 600-800 nm. A red-shift was observed in the characteristic absorption peak of V2O5 nanoflowers, which are attributed to the decrease of the bandgap of the samples.